Toward understanding the genetic bases underlying plant‐mediated "cry for help" to the microbiota. Issue 1 (14th March 2022) - Wang, Zhenghong; Song, Yi
Abstract: Canonical plant stress biology research has focused mainly on the dynamic regulation of internal genetic pathways in stress responses. Increasingly more studies suggest that plant‐mediated timely reshaping of the microbiota could also confer benefits in responding to certain biotic and abiotic stresses. This has led to the "cry for help" hypothesis, which is supported by the identification of plant genetic regulators integrating biotic/abiotic stress signaling and microbiota sculpting. Although diverse genetic mutants have been reported to affect microbiota composition, it has been challenging to confirm the causal link between specific microbiota changes and plant phenotypic outputs (e.g., fitness benefits) due to the complexity of microbial community composition. This limits the understanding of the relevance of plant‐mediated microbiota changes. We reviewed the genetic bases of host‐mediated reshaping of beneficial microbiota in response to biotic and abiotic stresses, and summarized the practical approaches linking microbiota changes and "functional outputs" in plants. Further understanding of the key regulators and pathways governing the assembly of stress‐alleviating microbiota would benefit the design of crops that could dynamically enlist beneficial microbiota under conditions of stress. Abstract : Diverse plant genes are positively involved in reshaping the microbiota in response to stresses, which might be a novel layer of stress tolerance strategies during evolution. Highlights: Plant‐associated microbiota affects diverse aspects of plant fitness and development, whereas how plants positively reshape a beneficial microbiota to enhance fitness is less studied. We reviewed the current understanding of the genetic mechanisms underlying plant‐mediated reshaping of the microbiota in response to stresses. Due to the complexity of the microbiota, it is challenging to confirm a causal link between microbiota changes and host phenotypes. We also reviewed the approaches to study the effect of microbiota changes on plant phenotypes.